(untitled) (Journal of Asian Development Studies, 2025)
The project manager’s leadership style is crucial in sustainable project outcomes in the current dynamic and complex project management environment. This paper aims to examine the role of servant leadership (SL) in project success (PS) with the mediating role of team cohesion (TC). Further, the study examines the moderation mediation model with top management support (TMS) as a moderator between SL and team cohesion. To achieve these objectives, a cross-sectional quantitative research design using a structured survey administered among project professionals in the construction sector was employed. The hypothesized relationship was assessed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The structural model shows that SL significantly and positively affects PS. Further, team cohesion mediates this relationship, emphasizing that servant leaders significantly enhance project outcomes through team cohesiveness and a collaborative work environment. Finally, the role of TMS in moderating the positive impact of SL and team cohesion demonstrates that in the presence of TMS, the effect of team cohesion is more substantial on project outcomes. Findings advance theoretical contributions in extending the theories of Leader-Member Exchange (LMX) and Resource Based View (RBV) in project management. The findings offer practical and managerial implications suggesting that SL practices in conjunction with strong TMS lead to enhanced team cohesion and better project performance.